2019
DOI: 10.1016/j.heliyon.2019.e02736
|View full text |Cite
|
Sign up to set email alerts
|

Biogas digestates are not an effective nutrient solution for hydroponic tomato (Lycopersicon esculentum L.) production under a deep water culture system

Abstract: The generation of energy through anaerobic digestion using animal manures is being promoted as an environmentally sustainable method of managing animal wastes. However, sustainability of biogas production is reliant on the sustainable utilization of the digestates that emanate from the process. Our study evaluated the effects of the biogas digestates on crop phytotoxicity and their fertilizer potential as a nutrient solution in hydroponic tomato production. Biogas digestates diluted up to 40% (v/v) resulted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Although this does not prevent the seed from germinating (as evidenced by the RSG values), it can constrain root development as roots may be exposed to stress from organic acid activity [11]. This phenomenon is similar to those results reported by Mupambwa et al [45], who achieved a 47-97% RRE value using different cultures at digestate doses under 10%.…”
Section: Digestate Maturitysupporting
confidence: 82%
“…Although this does not prevent the seed from germinating (as evidenced by the RSG values), it can constrain root development as roots may be exposed to stress from organic acid activity [11]. This phenomenon is similar to those results reported by Mupambwa et al [45], who achieved a 47-97% RRE value using different cultures at digestate doses under 10%.…”
Section: Digestate Maturitysupporting
confidence: 82%
“…(2019) [158] made similar observations using the liquid fraction of cow manure digestate on bioponically grown tomatoes. When used as the sole fertilizer, the digestate solution concentrated at 10%-the dilution ratio established to avoid phytotoxicity-did not contain sufficient N and P macro-nutrients for efficient plant growth.…”
Section: Use Of Anaerobic Digestates For Bioponic Cultivationmentioning
confidence: 64%
“…In Mupambwa et al's (2019) [158] study, a 10% concentrated digestate solution was found suitable for crop use, but phytotoxic when concentrated at 30 or 40%. In Phibunwatthanawong and Riddech's (2019) [41] study, only a concentration as low as 1% was found suitable.…”
Section: Use Of Anaerobic Digestates For Bioponic Cultivationmentioning
confidence: 98%
“…In this study, root length increased with BD soil application compared to IF and CO. Similarly, Mupambwa et al. (2019) , obtained elongated root length on tomato plants fertilised with BD.…”
Section: Discussionmentioning
confidence: 83%